Maternal characteristics and toddler food intake in the Sleman area during the COVID-19 pandemic - Ryveka, Aurellia (BKM Public Health and Community Medicine, 2021)
Objective: To determine the relationship between maternal characteristics, which consist of mother's knowledge, mother's employment status, and mother's education level, as well as food access and food intake of toddlers in Sleman Regency. Method: The method used in this study was a cross-sectional method with a purposive sampling technique on 45 pairs of mothers and children in 4 posyandu included in the working area of ​​Depok 3 Puskesmas, namely Nologaten, Kledokan, Janti Barat, and Karangmalang. Maternal characteristics and access to food were measured using a questionnaire, and food intake was measured using the SQ-FFQ questionnaire. The statistical test used was the Fisher exact test. Results: From the results of the descriptive analysis obtained, most of the respondents have a good level of knowledge (75.6%), respondents do not work (71.1%), respondents have a secondary education level (51.1%), respondents have difficult access to food (55,6%). Then, most toddlers have excess energy intake (80%), toddlers have excess protein intake (100%), toddlers have excess fat intake (86.7%), and toddlers have excess carbohydrate intake (71.1%). Mother's knowledge, mother's employment status, mother's education level, and food access are not related to the food intake of children under five. Conclusion: There is no significant relationship between maternal characteristics and access to food with toddler food intake.